One Health: enabler of effective prevention, control and elimination of emerging and re-emerging infectious diseases - Tianyun Li; Xiao-Nong Zhou; Marcel Tanner (Infectious Diseases of Poverty)
Abstract Emerging and re-emerging infectious diseases in different soci-ecological settings create unprecedented challenges for global public health and socio-economic development. The One Health concept is based on a systemic, transdisciplinary approach and hence captures the interactions between humans and animals, in a given socio-ecological setting. It could comprehensively address the human-animal-environment interface, the core of zoonotic diseases. Consequently, One Health approach is effective in controlling and eliminating the promoting factors of emerging infectious diseases (EIDs). We explored key principles for the prevention, control and elimination of EIDs through reviewing the transition of public health and global health strategies towards One Health and summarizing some successful experiences in effectively controlling EIDs. Recognizing heterogeneities and strengthening “surveillance-response systems” are the two key principles. It is recommended to promote health equity and conduct cost-effectiveness analysis to address the challenges of heterogeneity. Cross-sectoral collaboration and transdisciplinarity should be strengthened to facilitate the utilizing of systems thinking. Graphical abstract